Alex Gianopoulos: capstone - Gianopoulos, Alex, artist (Colorado State University. Libraries, 2014)
The artist's statement: My work is at its deepest root a reflection of my growth as a student and a person at Colorado State University. I put everything I have into my art and at the end of any given project I have grown as a result. Art to me is when someone dedicates time, passion and attention to a visual art. I do not view myself as a designer. I am wholeheartedly a student of art. I instead view myself as a passionate, young artist who wants to learn more about the trade than four years of school could ever teach me. The beautiful thing about what I have created here at Colorado State University isn't the aesthetics of it. It is the ability to grow and learn from it. My work at CSU is the foundation for the remainder of my art career. More important than any technical skill I developed was the development of my thought process. I learned how I think, how to challenge it, and how to grow from that. I do not know exactly where I fit in the context of contemporary art. I do not compare myself next to other artists. What makes beautiful art is the expression of that "thing" that makes us all human. Instead of comparing myself to others, I try to communicate with myself to express the vision of my art that makes me so undeniably unique. I believe it is that uniqueness that ironically connects us all. I want to thank all of my professors for helping me grow. Specifically, I wish to thank Patrice Sullivan, John Gravdahl, and Erika Osborne. Our interactions made me grow as a student, an artist, and a human being.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.